2016
DOI: 10.1186/s12978-016-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of community level interventions for pre-eclampsia: perspectives, knowledge and task-sharing from Nigeria, Mozambique, Pakistan and India

Abstract: Hypertensive disorders of pregnancy (HDP), particularly pre-eclampsia and eclampsia, remain one of the leading causes of maternal mortality and are contributory in many foetal/newborn deaths. This editorial discusses a supplement of seven papers which provide the results of the first round of the CLIP (Community Level Interventions for Pre-eclampsia) Feasibility Studies. These studies report a number of enablers and barriers in each setting, which have informed the implementation of a cluster–randomized trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Community health workers provide a potential first line of intervention as they have been shown to have sufficient knowledge and ability to identify women with preeclampsia and administer initial treatment. [26][27][28] Interventions will also need to focus on demystifying the prevalent myths and promote a more scientific understanding of the condition and eventually this knowledge could serve as cues for action.…”
Section: Discussionmentioning
confidence: 99%
“…Community health workers provide a potential first line of intervention as they have been shown to have sufficient knowledge and ability to identify women with preeclampsia and administer initial treatment. [26][27][28] Interventions will also need to focus on demystifying the prevalent myths and promote a more scientific understanding of the condition and eventually this knowledge could serve as cues for action.…”
Section: Discussionmentioning
confidence: 99%
“…Key enablers included simulation training, effective provider communication, and physician leadership. Other studies in low-resource settings have also identified participatory learning approaches [35], teamwork among doctors and nurses [3, 32, 36], and effective leadership [13] as facilitators of improved obstetric and emergency care. We found that communication techniques, such as the two-challenge rule, and clinical discussions can improve communication between providers, findings which are supported by results of related studies in high-resource settings [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Marked by high blood pressure (BP) and the presence of albumin in urine, preeclampsia is a risk factor for the potential development of severe preeclampsia or full-blown eclampsia and should be monitored. Management of SPE/E poses a challenge in low- and middle-income countries due to a lack of basic supplies, health worker shortages, limited competencies of frontline providers, and systems challenges that lead to delays in women receiving necessary treatment 2 4 . In Bangladesh, eclampsia-related conditions are the second leading direct cause of obstetric deaths and lead to 24% of all maternal deaths 5 .…”
Section: Introductionmentioning
confidence: 99%